Optimal State Feedback Controller for Balancing Cube - Piotrowski , Robert; Kowalczyk, Adam (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
In this paper, a nonlinear balancing cube system is considered which concept is based on an inverted pendulum. The main purpose of this work was the modelling and construction of a balancing cube with the synthesis of the control system. The control objectives included swing-up and stabilization of the cube on its vertex at an unstable equilibrium. Execution of the intended purpose required, firstly – deriving a cognitive mathematical model. It was based on the Lagrange method. Next, a mathematical model for control purposes was derived. The project of the physical model of the balancing cube was presented. A stabilization system based on a linear quadratic regulator (LQR) was developed. Moreover, a swing-up mechanism was used to bring the cube close to the upper equilibrium point. The algorithm switching condition was important to enable the correct functioning of the system. The developed control system was verified in the Matlab environment. Finally, verifying experiments and comparison between models (mathematical and physical) were performed.